Measuring the Stability of Supramolecular Complexes in the Proximity of Single‐Walled Carbon Nanotubes - Dr. Teresa Naranjo; Julia Villalva; Prof. Emilio M. Pérez (ChemistryOpen, 2020)
Abstract Invited for this month's cover is Emilio M. Pérez from IMDEA Nanociencia in Madrid. The cover picture shows the supramolecular association of an ammonium guest to a crown‐ether host which is covalently attached to a SWNT. In our manuscript, we show that the corresponding “KPOW!!” would be significantly louder for the binding of the free species in solution, in the absence of the SWNT. Read the full text of their Communication at 10.1002/open.202000018.